An isolated metachronous metastasis to the adrenal gland from a pancreatic neuroendocrine tumor: A case report. (2017) - Sakuma, Yasunaru; Sata, Naohiro; Endo, Kazuhiro; Yasuda, Yoshikazu; Yokota, Shinichiro; Hosoya, Yoshinori; Shimizu, Atsushi; Fujii, Hirofumi; Matsubara, Daisuke; Fukushima, Noriyoshi; Asakawa, Shoko; Shimada, Yuuki Kawarai; et al.
Highlights: This is the first patient reported with a metastasis to the spleen from a pNET[1] . Spleen metastases are extremely rare and are usually seen with disseminated disease. This is the first report of an isolated metachronous metastasis to the adrenal gland from a pNET, which appeared after 90 months. Serum PIVKA levels have never been reported in a patient with pNET. In this patient, serum PIVKA level was elevated at the time of diagnosis of 5/7 recurrences and returned to baseline levels following treatment. This suggests that PIVKA may be a useful tumor marker in patients with pNET, and deserves further study. Abstract: Introduction: Pancreatic neuroendocrine tumors are rare. Treatment includes aggressive local management of the primary lesion and metastases, and systemic somatostatin. This is the first report of an isolated metachronous metastasis to the adrenal gland from a pancreatic neuroendocrine tumor that presented 90 months after the primary tumor. Presentation of case: The patient presented as a 53yo man with a left upper quadrant mass and synchronous metastases to the spleen and liver (pancreatic neuroendocrine tumor T4N0M1, Stage IV), which were resected (CD56-, synaptophysin+, chromogranin+, Ki-67 < 1%). Over the next 90 months, he underwent five procedures to treat hepatic recurrences (2 liver resections and 3 percutaneous radiofrequency ablations). Serum PIVKA levels were elevated prior to treatment of four of six lesions and returned to baseline after therapy. He presents now, asymptomatic, with a right adrenal mass found on routine imaging and no other lesions. Serum PIVKA was elevated to 44 mg/dL. The adrenal gland was resected and shown to be a metastasis (CD56+, synaptophysin+, chromogranin+, Ki-67 15–20%). Discussion: This patient's clinical course reflects aggressive local therapy of the primary lesion and multiple metastatic lesions to three organs (liver, spleen, adrenal) over nearly eight years. The utility of serum PIVKA levels in patients with pancreatic neuroendocrine tumors is not previously reported and needs further investigation. Conclusion: This patient has a pancreatic neuroendocrine tumor with metastases to the spleen, liver and adrenal gland and elevated PIVKA levels with recurrent disease. These unique clinical features add to the diversity of clinical presentation of these rare tumors.